2016
DOI: 10.1002/anie.201609390
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Friedel–Crafts Alkylation/Lactonization Reaction of Naphthols with 3‐Trifluoroethylidene Oxindoles: The Asymmetric Synthesis of Dihydrocoumarins

Abstract: Naphthols and 3-trifluoroethylidene oxindoles were found to undergo an asymmetric Friedel-Crafts alkylation/lactonization reaction, catalyzed by only 2.5 mol % of a quinine-derived squaramide catalyst, to afford the corresponding α-aryl-β-trifluoromethyl dihydrocoumarin derivatives in high yields (up to 99 %) with excellent enantio- and diastereoselectivities (up to 98 % ee, >20:1 d.r.). Importantly, the lactonization proceeded by nucleophilic attack of the naphthol hydroxy group at the amide motif of the oxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Such an uncommon behaviour of amide C-N bond was also recently detected by Zhao and co-workers during their studies concerning the organocatalytic Friedel-Crafts/lactonization domino reaction ( Scheme 28 ) [ 64 ]. Actually, the authors reported a remarkable example of the employment of squaramide catalophore XXX in the asymmetric synthesis of dihydrocoumarins, a ubiquitous scaffold in bioactive natural products.…”
Section: Squaramide Catalystssupporting
confidence: 62%
“…Such an uncommon behaviour of amide C-N bond was also recently detected by Zhao and co-workers during their studies concerning the organocatalytic Friedel-Crafts/lactonization domino reaction ( Scheme 28 ) [ 64 ]. Actually, the authors reported a remarkable example of the employment of squaramide catalophore XXX in the asymmetric synthesis of dihydrocoumarins, a ubiquitous scaffold in bioactive natural products.…”
Section: Squaramide Catalystssupporting
confidence: 62%
“…In 2013, Jia and co‐workers reported an elegant ring‐opening cascade reaction of methyleneindolinone with isocyanide to generate quinoline skeletons . Thereafter, Zhao and Hu developed an asymmetric cascade reaction of naphthols and 3‐trifluoroethylidene oxindoles to install dihydrocoumarin skeletons by a sequential intramolecular amide C−N bond‐cleavage and esterification process . Despite these advances in the ring‐opening of 3‐oxindole derivatives, assembling spirooxindole through ring‐opening reactions is still surprisingly underdeveloped.…”
Section: Figurementioning
confidence: 99%
“…The enantioselective Friedel-Crafts reaction enables access to many valuable indole derivatives showing biological activity [18], like 2-and 3-substituted indoles [19], indoloquinolines [20] and spirooxindoles [21], and to the broad spectrum of other relevant molecules like dihydroisoquinolin-3-ones [22], (+)-aflatoxin B 2 [23], Dalesconol A and B [24], steroids [25], dihydrocoumarins [26] and trinuclear ferrocenes [27].…”
Section: Introductionmentioning
confidence: 99%